Contemporary financial management - McGuigan, James R.; Moyer, R. Charles; Kretlow, William J. (Cincinnati, OH : South-Western College, 2001)
This book is divided into five parts: Introduction; Determinants of valuation; The capital investment decision; The cost of capital, Capital structure, and dividend policy; Working capital management and financial forecasting; Advanced topics in contemporary financial management.
Keywords: Finance; Business enterprises; Corporations; Corporations -- Finance; Business enterprises -- Finance -- Case studies